Continuity of Care During COVID-19 Lockdown: A Survey on Stakeholders' Experience With Telerehabilitation - Assenza, Carla; Catania, Hilenia; Antenore, Clementina; Gobbetti, Tiziana; Gentili, Paola; Paolucci, Stefano; Morelli, Daniela (Frontiers in Neurology, 2021)
Objective. To explore professionals, adult patients and children’s caregivers perception and satisfaction with telerehabilitation during Covid-19 lockdown. Design. An observational transversal study on a web-based survey was conducted in order to explore participants’ perception and satisfaction of telerehabilitation during Covid-19 lockdown. Setting. The study was conducted at our Outpatient Neurorehabilitation Service. Subjects. All rehabilitation professionals, adult patients, children’s caregivers who accepted telerehabilitation were recruited. Interventions. Participants had to respond to the Client Satisfaction Questionnaire-8 and to a purpose-built questionnaire on their perception and satisfaction of the service provided. Main measures. Data was analyzed by qualitative statistics and logistic regression models. Results. All 144 caregivers, 25 adult patients and 50 professionals reported a medium-high level of perception and a high level of satisfaction. Results showed a correlation among caregivers of children aged 0-3 and feeling overwhelmed with remote care (OR=3.27); a low perception of telerehabilitation for enhancing goals (OR=6.51) and a high perception of feeling helped in organizing daily activity (OR=2.96). For caregivers of children aged over 6 years changes in the therapy plan was related to a low perception of feeling in line with the in-person therapy (OR=2.61 and OR=9.61) and a low satisfaction (OR=5.54 and OR=4.97). Changes in therapy resulted related to concern (OR=4.20). Caregivers under 40 and professionals showed a high probability to perceive telerehabilitation as supportive (OR=2.27 and OR=5.68). Level of experience with remote media showed to influence perception and satisfaction. Interpretation. Telerehabilitation can be a useful practice both during a health emergency and in addition to in-presence therapy.